Magnetism and magnetoresistance of single Ni–Cu alloy nanowires - Costas, Andreea; Florica, Camelia; Matei, Elena; Toimil-Molares, Maria Eugenia; Stavarache, Ionel; Kuncser, Andrei; Kuncser, Victor; Enculescu, Ionut (Beilstein Journal of Nanotechnology, 2018)
Arrays of magnetic Ni–Cu alloy nanowires with different compositions were prepared by a template-replication technique using electrochemical deposition into polycarbonate nanoporous membranes. Photolithography was employed for obtaining interdigitated metallic electrode systems of Ti/Au onto SiO2/Si substrates and subsequent electron beam lithography was used for contacting single nanowires in order to investigate their galvano-magnetic properties. The results of the magnetoresistance measurements made on single Ni–Cu alloy nanowires of different compositions have been reported and discussed in detail. A direct methodology for transforming the magnetoresistance data into the corresponding magnetic hysteresis loops was proposed, opening new possibilities for an easy magnetic investigation of single magnetic nanowires in the peculiar cases of Stoner–Wohlfarth-like magnetization reversal mechanisms. The magnetic parameters of single Ni–Cu nanowires of different Ni content have been estimated and discussed by the interpretation of the as derived magnetic hysteresis loops via micromagnetic modeling. It has been theoretically proven that the proposed methodology can be applied over a large range of nanowire diameters if the measurement geometry is suitably chosen.
Keywords: nanowires; magnetic properties; magnetoresistance